ANALYSIS OF FACTORS AFFECTING LABOR EFFICIENCY IN OIL PALM HARVESTING AT PT ASN KEBUN UJONG LAMIE, NAGAN RAYA DISTRICT - Darwin; Teuku Athaillah (CV. Radja Publika, 2023)
Labor efficiency is all the efforts made by each member in balancing the amount of labor with the production produced. The purpose of this study was to determine the labor efficiency of oil palm harvesters at PT ASN Kebun Ujong Lamie, Nagan Raya Regency. This study uses a quantitative research method with multiple linear regression analysis method. The sampling technique used was purposive sampling. The sample in this study amounted to 19 respondents. The results showed that partially with a 95% confidence level the premium variable had an effect on the labor efficiency of oil palm harvesters, and age and education level had no effect on the efficiency of the palm oil harvesters. Meanwhile, the age, education level, and premium variables simultaneously affect the labor efficiency of oil palm harvesters.